PENGARUH LATIHAN PASRAH DIRI TERHADAP PERBAIKAN DISFUNGSI EREKSI (Studi pada Penderita Gagal Ginjal Kronik dengan Simtom Depresi yang Menjalani Hemodialisis Rutin) - , dr. Agus Susiloningsih, dr. Agus Siswanto, SpPD-Kpsi ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Patients with chronic renal failure (CRF) had both of physical, psychological and social stressors, so vulnerable to the emergence of depression symptoms. Symptoms of depression and other conditions related to CRF lead to erectile dysfunction in male patients. âLatihan Pasrah Diri (LPD)â is a part of the Complementary and Alternative Medicine (CAM) in the management strategies of depression symptoms that combines relaxation and âdhzikrâ (repetitive prayer) focusing on breathing and the words contained in the âdhzikrâ to evoke the relaxation response, which expected to improve the depression symptoms. This study was conducted to determine the effect of LPD on the improvement of symptoms of depression and erectile dysfunction on hemodialysis patients with symptoms of depression. A Randomized Placebo Controlled Trial (RCT) design was conducted in the Hemodialysis Unit of Dr. Sardjito hospital between January and May 2012. Data distribution was tested using Shapiro-Wilk statistical test. The Beck Depression Inventory (BDI) mean score and the IIEF-5 mean score difference of each group was tested by t-test for paired group if the distribution of data was normal or Wilcoxon test if the distribution was not normal. Effect of LPD on BDI mean score and the IIEF-5 mean score differences of the treatment and control groups were tested using independent t-test. The differences were significant if p value <0.05 with 95% confidence of interval. The results of this study were present the characteristics of subjects by age, sex, educational level, occupation, smoking status, BMI, comorbids, therapy, lipid profile, blood urea and creatinine, hemoglobin, liver function, BDI score and IIEF-5 score. This research will demonstrate the benefits of LPD on the improvement of depression symptoms and erectile dysfunction on hemodialysis patients.